2009
DOI: 10.1007/s11064-009-0023-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteomics Analysis of Specific Carbonylated Proteins in the Temporal Cortex of Aged Rats: The Deterioration of Antioxidant System

Abstract: Oxidative stress plays a pivotal role in normal brain aging and various neurodegenerative diseases, including Alzheimer's disease (AD). Irreversible protein carbonylation, a widely used marker for oxidative stress, rises during aging. The temporal cortex is essential for learning and memory and particularly susceptible to oxidative stress during aging and in AD patients. In this study, we used 2-DE, MALDI-TOF/TOF MS, and Western blotting to analyze the differentially carbonylated proteins in the rat temporal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
(79 reference statements)
0
21
0
Order By: Relevance
“…These changes correlated with age related deterioration in learning and memory 145 . An age associated increase in the carbonylation of aconitase and ATP synthase is found in rats as well 146 69,147 . In addition, adenine nucleotide translocator, voltage-dependent anion channel, glutamate oxaloacetate transaminase, and aconitase are more susceptible to oxidative stress induced carbonylation in the mitochondria of aged rat brain 148 .…”
Section: Biological Consequences Of Protein Oxidationmentioning
confidence: 91%
See 1 more Smart Citation
“…These changes correlated with age related deterioration in learning and memory 145 . An age associated increase in the carbonylation of aconitase and ATP synthase is found in rats as well 146 69,147 . In addition, adenine nucleotide translocator, voltage-dependent anion channel, glutamate oxaloacetate transaminase, and aconitase are more susceptible to oxidative stress induced carbonylation in the mitochondria of aged rat brain 148 .…”
Section: Biological Consequences Of Protein Oxidationmentioning
confidence: 91%
“…150 Carbonyl levels of ten proteins increased significantly in the temporal cortex of aged rats has been observed as well. 151 …”
Section: Biological Consequences Of Protein Oxidationmentioning
confidence: 99%
“…In a differential proteomic analysis, PRX 1 from aged rat temporal cortex tissue is carbonylated, suggesting that this enzyme contributes to the decline in cognitive function that occurs during aging (431). PRX II also has been shown to be upregulated in response to increase Ab levels during AD, with the purpose of protecting neurons against Ab-induced toxicity (456).…”
Section: Massaad and Klannmentioning
confidence: 99%
“…A number of experimental evidence indicate that increased rate of free radical generation and decreased efficiency of the reparative/degradative mechanisms, such as proteolysis, both are factors which primarily contribute to age-related elevation in the level of oxidative stress and brain damage. With respect to this, it has been suggested that decreases in levels of enzymes which ordinarily protect neuronal cells against oxidative stress with age may be responsible for increased levels of free-radical damage in the brain, or that these enzymes themselves are susceptible to inactivation by free radical molecules which increase with age in the brain [27]. During aging a number of enzymes accumulate as catalytically inactive or less active forms.…”
Section: The ''Free Radical Hypothesis'' Of Agingmentioning
confidence: 99%